2017
DOI: 10.1108/wje-10-2016-0109
|View full text |Cite
|
Sign up to set email alerts
|

Geometrically nonlinear analysis of shells by various dynamic relaxation methods

Abstract: Purpose Numerical experiences reveal that the performances of the dynamic relaxation (DR) method are related to the structural types. This paper is devoted to compare the DR schemes for geometric nonlinear analysis of shells. To achieve this task, 12 famous approaches are briefly introduced. The differences among these schemes are between the estimation of the time step, the mass and the damping matrices. In this study, several benchmark structures are analyzed by using these 12 techniques. Based on the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Especially, MIP Newton method can be well applied to high slenderness structures. Because of the importance of nonlinear solvers with respect to computational mechanics and their wide application, many solvers have been proposed to reduce number of iterations per load step and computation as the following: optimization-based iterative technique 6 and residual areas-based iterative technique, 7 dynamic relaxation techniques, [8][9][10] multipoint methods-based path following techniques, 11 a novel method to transform the discretized governing equations, 12 a data-driven nonlinear solver (DDNS), 13 an improved predictor-corrector method, 14 Koiter-Newton method with a superior performance for nonlinear analyses of structures, 15,16 etc. It is observed that employing time series prediction to reduce number of iterations of nonlinear solvers is very rare except the DDNS.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, MIP Newton method can be well applied to high slenderness structures. Because of the importance of nonlinear solvers with respect to computational mechanics and their wide application, many solvers have been proposed to reduce number of iterations per load step and computation as the following: optimization-based iterative technique 6 and residual areas-based iterative technique, 7 dynamic relaxation techniques, [8][9][10] multipoint methods-based path following techniques, 11 a novel method to transform the discretized governing equations, 12 a data-driven nonlinear solver (DDNS), 13 an improved predictor-corrector method, 14 Koiter-Newton method with a superior performance for nonlinear analyses of structures, 15,16 etc. It is observed that employing time series prediction to reduce number of iterations of nonlinear solvers is very rare except the DDNS.…”
Section: Introductionmentioning
confidence: 99%
“…Rezaiee-Pajand and Rezaee (2014) have also suggested a fictitious time step for the kinetic DR method. In recent works, Rezaiee-Pajand and Estiri (2016a, 2016b, 2016c, 2017 conducted some comparative studies on three-dimensional frames, shells and bending plates. Furthermore, these researchers suggested a technique to find equilibrium paths by minimizing external work in the DR method (Rezaiee-Pajand and Estiri, 2016a, 2016b, 2016c.…”
Section: Introductionmentioning
confidence: 99%